2020
DOI: 10.1186/s41983-020-00183-2
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and structural magnetic resonance imaging in chronic stroke and the relationship with upper extremity motor function

Abstract: Background Recovery of upper extremity (UE) motor function after stroke is variable from one to another due to heterogeneity of stroke pathology. Structural and biochemical magnetic resonance imaging of the primary motor cortex (M1) have been used to document reorganization of neural activity after stroke. Objective To assess cortical biochemical and structural causes of delayed recovery of UE motor function impairment in chronic subcortical ischemic stroke patients. Methodology A cross-sectional study with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…The number of smokers included in the studies ranged from 10 19 to 137 (19) . Regarding the country of origin of the studies, one was from Brazil (14) , two were from Turkey (20,21) , two were from India (7,22) , two were from Egypt (13,23) , and one from Germany (19) . Due to the nature of the guiding question, all included studies used convenience samples.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The number of smokers included in the studies ranged from 10 19 to 137 (19) . Regarding the country of origin of the studies, one was from Brazil (14) , two were from Turkey (20,21) , two were from India (7,22) , two were from Egypt (13,23) , and one from Germany (19) . Due to the nature of the guiding question, all included studies used convenience samples.…”
Section: Resultsmentioning
confidence: 99%
“…A summary of the characteristics of the eight included studies can be found in Chart 1. Regarding the test performed, three performed BAEP (7,14,22) , four performed P300 (19)(20)(21)23) , and one performed Mismatch Negativity (MMN) and P300 (13) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations